Landscape and gender : Traversing the contested and mediated 'spaces' in India - Chatterjee, Sharmistha Ed.; Dey, Moumita Ed. (Delhi : Primus Books, 2024)
Landscape and Gender delves into the intricacies of contested and mediated 'spaces' through a gendered lens. Bringing together a range of subjects-archaeology, history, cultural geography, and urban studies-the chapters here examine the connections between landscape and gender within a spatio-temporal framework unique to India. The volume explores spaces that are regulated and subordinated by agencies, and which reinforce gender gaps in quotidian landscapes.
Keywords: Feminist geography -- India; Gender identity -- India -- West Bengal; Sex role -- India